Different Treatment Protocols of Retained Fetal Membranes and its Effect on Serum Profile, Uterine Involution and Postpartum Fertility in Cows - Shah, AI; Patel, DM; Sarvaiya, NP; Madhira, SP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This study was undertaken on 36 freshly calved cows randomly divided into 6 equal groups under field conditions. Cows of group-VI that  shed placenta within 8-12 hours postpartum naturally served as healthy control. The cows with retained fetal membranes (RFM, n = 18) for  more than 12 hrs were managed either by manual removal of placenta without antibiotics (group-I), parenteral antibiotic (Ceftiofur 1 g i/m)  for three consecutive days (group-II) or a combination of both (group-III). In group-IV and group-V, cows were administered with Inj.  Oxytocin @ 50 IU i/m and Inj. Dinoprost tromethamine (PGF2α) @ 25 mg i/m, respectively, immediately after parturition and time of  placental shedding was recorded. The overall prevalence of Brucellosis by RBPT was found to be 5.55 % amongst these 36 animals.  The placental expulsion in groups following medicinal treatment was found to be 50 (3/6) % in Ceftiofur alone by 3 days (group-II),  and 66.67 (4/6) % in Oxytocin (group-IV) and 100 (6/6) % in PGF2α inj. (group-V) groups within 12 hrs. The time of uterine involution  in groups I to VI was found to be 42.00 ± 1.94, 39.50 ± 0.99, 40.67 ± 1.39, 38.33 ± 1.55, 37.50 ± 1.02 and 37.33 ± 1.76 days, respectively,  while the interval for the appearance of first postpartum estrus was 54.83 ± 2.06, 51.00 ± 1.05, 52.17 ± 1.96, 50.17 ± 2.03, 48.67 ± 1.90  and 49.17 ± 1.55 days, respectively, which did not vary statistically. The mean serum progesterone profile obtained on day 0 and day 21  postpartum was statistically non-significant between groups. However, it was significantly (p
Keywords: Cows; Retained fetal membranes; Therapeutic approaches; Serum progesterone and Minerals; Postpartum fertility